Frasa Problematik beba'al hamon dalam Kidung Agung: Interpretasi dan Implikasi - Prabowo, Paulus Dimas (Sekolah Tinggi Teologi Baptis Indonesia, 2023)
The phrase ????????? ??????? (beba'al hamon) in Song of Songs 8:11 is a problematic phrase. First, this phrase is interpreted as a geographical location in the LAI version of the Bible and even the English version, but the location is still unclear and is still debated today. Second, the phrase has been interpreted variously, such as: the husband of many people, the Canaanite fertility god, and the god of the Tyrians and Carthaginians. Third, ancient manuscripts that are older than the Masoretic Text, namely the Septuagint, Aquila, Symmachus, Vulgate and Peshitta, mostly have different translations and meanings of these phrases. Based on these three problems, the research question in this article is: what is the correct interpretation of the phrase ????????? ??????? (beba?al hamon) and its implications for the interpretation of the Song of Songs 8:11-12? This article aims to interpret the meaning of the phrase ????????? ??????? (beba?al hamon) and its implications in the interpretation of the Song of Songs 8:11-12. The methods used are comparative analysis of manuscripts, syntactic analysis, and literary analysis of poetry with an emphasis on structure and parallelism. As a result, the phrase ????????? ??????? (beba?al hamon) has the meaning 'as the owner of many people' and Song of Songs 8:11-12 wants to explain that Solomon's love for the Sulamite girl was liberating, where his wealth and power in managing the vineyard had an impact on the release of the Sulamite girl from a poor life with his brothers to a life of freedom.